The value of may as an evidential and epistemic marker in English medical abstracts - Alonso-Almeida, Francisco; Cruz-García, Laura (Studia Anglica Posnaniensia, 2012)
Our article addresses the issue of the relationship between epistemic modality and evidentiality. Earlier works such as Lazard (2001) claim that English does not hold grammatical markers for the source of knowledge in contrast to other languages, e.g. Quechua, that seem to do so. Dendale and Tasmowski (2001), however, think that grammatical evidentials are possible in English, and Aikhenvald (2004) admits that modal verbs in English are a borderline case. In our article, we seek to explore the use of may and might in a corpus of medical abstracts to demonstrate (i) their value as grammatical evidential markers, and (ii) their value as epistemic markers that show the author's attitude to the proposition manifested. In doing so, we follow Cornillie (2009), who defines these two concepts as independent categories. The results of our analyses indicate that these modals may be used as grammatical markers of evidentiality, regardless of other semantic and pragmatic meanings.